An Analysis of Clinical Effectiveness of Different Types of Direct Restorative Materials in Permanent Posterior Teeth - Harish, Lakshmi (Archive of Orofacial Data Science, 2024)
AIM: To compare and evaluate the effectiveness of direct restorative materials in permanent posterior teeth based on different clinical outcomes and to review how various factors influence them. METHODS: An intensive search using the PICOS elements was conducted through PubMed and Cochrane databases. Seventeen studies were selected and analyzed using primary and secondary outcomes. RESULTS: Amalgam restorations showed slightly better longevity compared to composite resin and glass ionomer cement restorations. However, under certain conditions, composite resins and glass ionomer cement restorations perform equally well. Failures in composite resin restorations were consistently due to secondary caries, primary caries, postoperative sensitivity, marginal defects, and marginal discoloration. Glass ionomer cement restorations failed consistently due to loss of retention and surface texture. Amalgam restorations mainly failed due to poor color match and tooth fracture. Significantly higher restoration failure rates were observed in medium or large-sized cavities with two or more surfaces involved, molars, children, teenagers, elderly patients, and those with high caries risk or poor oral hygiene. CONCLUSION: Patient-, oral-, and dentist-related factors significantly impact the performance and longevity of direct restorative materials. No material currently meets all criteria of an ideal material, as each has its advantages, disadvantages, and preferred indications.